2021
DOI: 10.1177/10963480211067275
|View full text |Cite
|
Sign up to set email alerts
|

Is Your Food Organic? Examining the Role of Food Aesthetics in Restaurant Marketing

Abstract: Many restaurants believe that an aesthetically pleasing food presentation can help attract customers and elevate their evaluations. Yet the effectiveness of expressive aesthetics and the psychological processes associated with its use are not well understood in hospitality research. This study adopts a consumer behavior lens to explore how expressive aesthetics affects consumers’ decision making about organic versus conventional food in the restaurant setting. Findings reveal that the expressive aesthetics str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…According to [29], this theory directly supports the dimension of food presentation in food quality research. It suggests that when restaurants present their dishes in visually appealing ways -with thoughtful arrangement, vibrant colors, attractive garnishesthey can create positive emotions among consumers.…”
Section: Food Presentationmentioning
confidence: 74%
“…According to [29], this theory directly supports the dimension of food presentation in food quality research. It suggests that when restaurants present their dishes in visually appealing ways -with thoughtful arrangement, vibrant colors, attractive garnishesthey can create positive emotions among consumers.…”
Section: Food Presentationmentioning
confidence: 74%
“…There is another stream of research examining moderators of organic food consumption, such as gender, food prices, consumers' perceived trust, and individual differences in environmental concerns and knowledge (Bonn et al, 2016;Jeong & Jang, 2019;Shin & Mattila, 2019). Recently, researchers have begun to ponder the success of marketing strategies in endorsing organic food, including advertising labels and claims (Hidalgo-Baz et al, 2017;Lee et al, 2018), persuasive messaging (Kareklas et al, 2014;Septianto et al, 2019), and food presentation (Yu & Liu, 2021). However, the role of sustainability in such a fast-growing food consumption trend has not been thoroughly explored.…”
Section: Sustainability Through Marketing Organic Food Consumptionmentioning
confidence: 99%
“…Accordingly, from the perspective of organic food presentation, it is encouraged to present with a lower level of expressive aesthetics to emphasize its sustainability. In particular, organic food marketers should minimize artificial ingredient alteration and instead maintain a rustic, authentic appearance to highlight the product's environmental benefits (Yu & Liu, 2021). Common strategies like the use of garnishes should be discouraged in organic restaurants as they contradict the philosophy of environmental sustainability that these establishments strive to convey.…”
Section: Food Presentationmentioning
confidence: 99%
“…Previous studies have shown that visual aesthetic perception affects consumers' decisionmaking. For example, in restaurants, consumers will choose aesthetically pleasing dining atmospheres, which largely affect consumers' hedonic needs (Yu and Liu, 2021). Consumers' positive visual aesthetic perception can provide a pleasant experience for consumers, thereby improving consumers' purchase intentions (Kim et al, 2021, Jin et al, 2022, Hou and Pan, 2023.…”
Section: Visual Aesthetic Perception Hypothesismentioning
confidence: 99%